2019
DOI: 10.3389/fnhum.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Human Sensory LTP Predicts Memory Performance and Is Modulated by the BDNF Val66Met Polymorphism

Abstract: Background : Long-term potentiation (LTP) is recognised as a core neuronal process underlying long-term memory. However, a direct relationship between LTP and human memory performance is yet to be demonstrated. The first aim of the current study was thus to assess the relationship between LTP and human long-term memory performance. With this also comes an opportunity to explore factors thought to mediate the relationship between LTP and long-term memory. The second aim of the current study was to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 61 publications
(97 reference statements)
1
18
0
Order By: Relevance
“…Behaviourally, we replicated previous work reporting that Met allele carriers have 31 VAL66MET GENOTYPE INFLUENCES RECOGNITION ERPs reduced accuracy compared to Val/Val individuals on recognition memory tasks Hariri et al, 2003;Spriggs et al, 2019) . More specifically, we found anecdotal evidence in support of Val/Val individuals outperforming Met allele carriers on the item-recognition portion of our task.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Behaviourally, we replicated previous work reporting that Met allele carriers have 31 VAL66MET GENOTYPE INFLUENCES RECOGNITION ERPs reduced accuracy compared to Val/Val individuals on recognition memory tasks Hariri et al, 2003;Spriggs et al, 2019) . More specifically, we found anecdotal evidence in support of Val/Val individuals outperforming Met allele carriers on the item-recognition portion of our task.…”
Section: Discussionsupporting
confidence: 87%
“…For example, a single nucleotide polymorphism (SNP) known as the Val66Met SNP (rs6265), occurs within the gene coding for brain-derived neurotrophic factor (BDNF) and has been previously related to reduced accuracy on a large number of memory tasks (Dempster et al, 2005;Egan et al, 2003;Hariri et al, 2003;Kennedy et al, 2015;Lamb, Thompson, McKay, Waldie, & Kirk, 2015) . Several recent studies have reported that carriers of this SNP perform worse than non-carriers on recognition memory tasks (Komulainen et al, 2008;Spriggs et al, 2019) . The Val66Met SNP is a non-synonymous SNP that results in a switch from a valine (Val) to methionine (Met) amino acid.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the processing of sensory information in simple tasks (e.g., visual sensory stimuli) is further modulated by attention [ 4 ]. Altered processing of sensory information can impact the activity of other systems (e.g., memory systems) [ 5 ], therefore, the N1b component may be a marker indicating the effects of attention on memory. The N1b component is a late phase of the N1 complex that is a negative ERP signal occurring ~170–190-ms post stimulus onset [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that individuals with at least one copy of the Val66Met minor allele (i.e., Val/Met and Met/Met) fare worse on learning and memory tasks (Bekinschtein, Cammarota, Izquierdo, & Medina, 2008;Lamb, Thompson, McKay, Waldie, & Kirk, 2015;Pang & Lu, 2004;Rattiner, Davis, & Ressler, 2005;Spriggs et al, 2019;Tyler, Alonso, Bramham, & Pozzo-Miller, 2002). For example, Egan et al (2003) reported that Met allele carriers performed significantly worse on episodic memory, as measured by the revised version of the Wechsler Memory Scale (WMS-R).…”
Section: Introductionmentioning
confidence: 99%